Significance of Lumbar MRI in Diagnosis of Sacral Insufficiency Fracture. Issue 8 (October 2021) - Graul, Isabel; Vogt, Sophia; Strube, Patrick; Hölzl, Alexander
Study Design: Retrospective observational study. Objective: The aim of the present study was to evaluate the role of lumbar magnetic resonance imaging (MRI) in the diagnostic algorithm of sacral insufficiency fractures (SIF). The primary objective was to compare the sensitivity in fracture detection and correct fracture classification according to MRI and computed tomography (CT). The secondary objective was to identify differences of additional pathologies found in MRI of the lumbar spine and the pelvis and their rates. Methods: A total of 943 patients (from 2010 to 2017) with fracture of the pelvic ring were screened. All patients without high-energy trauma and radiologic diagnostics consisting of X-ray, CT, and MRI of the pelvis or the lumbar spine including the sacrum were included. Differences in fracture detection and description in the various radiologic procedures were evaluated. Detection rates of additional pathologies in MRI of the pelvis and lumbar spine were recorded. Results: A total of 77 subjects were included. The sensitivities for SIF were 14% in X-ray and 88% in CT, and all fractures were detected in MRI. MRI showed a more complex fracture pattern compared with CT in 65% of the cases. Additional pathologies were seen in MRI of the lumbar spine (51%) and that of the pelvis (18%). Conclusions: We suggest performing MRI of the lumbar spine including the sacrum with coronal STIR (short tau inversion recovery) sequence for elderly patients with suddenly increasing low back pain at an early stage. This procedure might improve fracture detection, classification, and recognition of concomitant pathologies.